Mergers and Acquisitions: characterization and evolution in Brazil in the period 1992-2007 - Borges, Ana Claudia Giannini [UNESP]; Costa, Vera Mariza Henriques de Miranda [UNESP] (Sindicato Secretarias Estado Sao Paulo, 2023)
This article aims to identify and analyze the evolution of Mergers and Acquisitions (M&A) in Brazil, in the period from 1992 to 2007, in several activity sectors, registering their presence, in this period, in the geographic regions and still differentiating domestic and cross border. It was based on the hypothesis that M&A, in Brazil, were stimulated from the 1990s onwards, by factors of different orders, part of which affected the Brazilian economy and companies in general and others with specific impacts on certain companies. and sectors. This is a descriptive-exploratory, qualitative research, with qualitative and quantitative treatment. Secondary source data and information were used. The analysis of the evolutionary process was based on KPMG publications. Based on the data collected and compared with other theoretical and sectoral studies on M&A, it was possible to verify that, in order to understand this process, both the macro and microeconomic environments must be evaluated.
Keywords: Merger and Acquisition; M&A; Competitiveness; Brazil